Raising Independent, Self-Confident Kids : Nine Essential Skills to Teach Your Child or Teen. - Moss, Wendy (Wendy L.) (Life tools., 2017)
Parents who read this book will learn how to help their children deal with frustration, make decisions, and become confident, self-sufficient adults.